DISTANCE MAGIC GRAPHS - A SURVEY - Arumugam, S.; Froncek, Dalibor; Kamatchi, N. (IndoMS, 2011)
Let iG = (V;E)/i be a graph of order n. A bijection if : V rarr; 1, 2,...,n /iis called ia distance magic labeling /iof G if there exists a positive integer k such that iSigma; f(u) = k /i for all iv epsilon; V/i, where iN(v)/i is the open neighborhood of v. The constant k is called the magic constant of the labeling f. Any graph which admits ia distance magic labeling /iis called a distance magic graph. In this paper we present a survey of existing results on distance magic graphs along with our recent results,open problems and conjectures.DOI :Â http://dx.doi.org/10.22342/jims.0.0.15.11-26